Validation of a motion capture system for deriving accurate ground reaction forces without a force plate. Issue 1 (December 2016) - Fry, Andrew; Herda, Trent; Sterczala, Adam; Cooper, Michael; Andre, Matthew
Abstract Background Human movement such as physical work, exercise and sport activities can be analyzed to determine kinetic (force) and kinematic (motion) characteristics. In the past, proper assessment of force variables requires force plates that can limit the types of activities performed. Additionally, large amounts of data are often generated, requiring often tedious and time-consuming analyses and calculations. Therefore, the purpose of this project was to compare the vertical ground reaction forces obtained from a force plate with calculated GRFs derived from a motion capture system during body weight squats for five healthy men. Results After performing three body weight squats, vertical ground reaction forces in Newtons were calculated for each data point for the force plate and motion capture system data, and synchronized from the point of peak force. There were no significant differences (p  < .05) for peak force, lowest force, or mean force between trials or modalities (force plate or motion capture system). Comparison of force-time curves with regression analyses indicated excellent agreement between testing modalities (r  = 0.995, r 2  = 0.989, SEM = 11.1 N). Conclusions These results indicate that ground reaction forces can be accurately derived from a motion capture system without the use of a force plate. Additionally, the large volumes of raw data were easily and rapidly analyzed using the easily customized software program. These results indicate that intricate kinetic characteristics of human motion can be validly determined without being restricted to performing on a force plate.